Infrared thermal imaging based study of localized cold stress induced thermoregulation in lower limbs: The role of age on the inversion time. (December 2020) - Lahiri, B.B.; Bagavathiappan, S.; Philip, John
Abstract: Thermoregulatory control of human body temperature is of paramount importance for normal bodily functions. Exposure of the upper and lower limbs to localized cold stress can cause cold-induced injuries and often lower limbs are more susceptible to damages from cold-induced injuries. In this study, we use infrared thermal imaging to probe localized cold stress induced cutaneous vasoconstriction of lower limbs in 33 healthy subjects. The cold stress is actuated by applying ice to the plantar surfaces of the lower limbs for 180 s and after removal of the cold stress, infrared thermography is utilized to non-invasively monitor the time-dependent variations in vein pixel temperatures on the dorsal surfaces of the stimulated and non-stimulated feet. It is observed that the vein pixel temperature of the stimulated foot showed a non-monotonic variation with time, consisting of an initial decrease and the presence of an inversion time, beyond which temperature is regained. The initial decrease in vein pixel temperature of the stimulated foot is attributed to the reduced blood flow caused by the cold stress induced severe vasoconstriction. Beyond the inversion time, the vein pixel temperature is found to increase due to rewarming of the surrounding skin. Experimental findings indicate that the inversion time linearly increased with the age of the subject, indicating a reduced thermoregulatory efficiency for the aged subjects. This study provides a thermal imaging-based insight into the skin temperature re-distribution during the early stages of blood perfusion in lower limbs, after an exposure to a localized acute cold stress. Statistical analyses reveal that subject height, weight, body-mass index and gender do not influence the inversion time significantly. The experimental findings are important towards rapid evaluation of personnel fitness for deployment in extreme cold environment, treatment of cold-induced injuries and probing of thermoregulatory impairments. Graphical abstract: Image 1 Highlights: Effect of localized cold stress on feet is studied using infrared thermography. Vein pixel temperature of the stimulated foot initially decreased. Beyond inversion time vein pixel temperature increased due to rewarming. The inversion time linearly increased with subject age. No significant influence of height, weight, BMI and gender on inversion time.